D3 Versus D2 Lymphadenectomy in Right Hemicolectomy: A Systematic Review and Meta-analysis. (June 2022) - Liu, Sailiang; Li, Laiyuan; Sun, Haojie; Chen, Bojie; Yu, Minhao; Zhong, Ming
Purpose: D3 lymphadenectomy for right colon cancer improves oncological outcomes. This meta-analysis aimed to compare operation data, histopathological characteristics, perioperative conditions, and long-term survival after D3 and D2 lymphadenectomy in right hemicolectomy. Methods: We searched PubMed, Embase, and the Cochrane Library for relevant articles (up to March 31, 2020). Random-effects and fixed-effects meta-analysis models were used. Review Manager (RevMan) version 5.3 and Stata version 15.1 were used for pooled estimates. Results: After screening 714 articles, 7 articles with a total of 1368 patients were eligible for inclusion. Compared with D2, D3 lymphadenectomy improves results in terms of blood loss (weighted mean difference [WMD] = −20.63, 95% confidence interval [CI] −28.19 to −13.16, P < .01), harvested lymph nodes (WMD = 8.86, 95% CI 7.74 to 9.98, P < .01), 3-year overall survival (OS) (hazard ratio [HR] = 2.03, 95% CI 1.20 to 3.43, P < .01), 5-year OS (HR = 2.22, 95% CI 1.15 to 4.30, P = .02), and 5-year disease-free survival (DFS) (HR = 2.16, 95% CI 1.19 to 3.90, P = .01). There was no significant difference regarding operation time, anastomosis leakage, wound infection, overall morbidity, postoperative hospital stay, mortality, length of dissected colon, and 3-year DFS ( P >= .05). Conclusions: It is suggested in this review that D3 lymphadenectomy is superior to D2 lymphadenectomy in terms of blood loss, harvested lymph nodes, 3-year OS, 5-year OS, and 5-year DFS. The conclusion must be drawn with caution due to the limited number of included studies. Further RCTs are needed for stronger evidence.